THE STUDENTS’ ANXIETY FACTORS IN SPEAKING BY USING YOUTUBE AT MAN 5 MANDAILING NATAL - Daulay, Sholihatul Hamidah; Ismahani, Siti; Lubis, Nurul Atika (Universitas Pamulang, 2022)
The purpose of this study was to explore a variety of types of Students Anxiety in Speaking English in the tenth grade of MAN 5 Mandailing Natal, as well as the factors that contributed to the Student's anxiety in speaking English in the tenth grade of MAN 5 Mandailing Natal by using youtube. The objection is the first year of the 2020/2021 school year. This method was a qualitative study that used observations and interviews to collect data. the data analysis in this study was descriptive analysis, data reduction, data display, conclusion, or verification. Based on the research it found that there were three types of student anxiety in learning English at the tenth-grade of MAN 5 Mandailing Natal, they are State anxiety, where the students feel panic and could stress when they want to speak in English, trait anxiety, where the students feel nervous when the students could not understand the teacher explanation, and specific-situation Anxiety, where the students should do examination about speaking. three factors caused the student's anxiety in learning English in the tenth grade of MAN 5 Mandailing Natal. these factors are communication apprehension, where the students could not speak English because they have little experience with English and do not always practice English, test anxiety, where the students feel anxious because they have to do the test that the teacher gives them, and fear of negative evaluation when students afraid about others people comment to them.